(untitled) (Singaporean Journal of Business Economics and Management, 2013)
Labour unrest in the form of strike actions in both public and private corporate organizations underscore the importance employees attach to the issue of compensation. As a result, the human resource functions of many corporate organizations are challenged to develop and implement effective compensation schemes which will lead to the achievement of organizational goals. This study seeks to examine the relationship between compensation and productivity in the banking industry in Ghana. Using case study approach, a descriptive survey was carried out to collect data from employees of Ghana Commercial Bank in the Greater Accra Region of Ghana. Data was analysed in terms of descriptive statistics. Pearson chi square was used to test the significance of relationship between employee compensation and productivity. The results indicated a significant relationship between compensation and productivity. Keywords: employee compensation, motivation, productivity.